AN OVERVIEW OF THE ORGANIZATIONAL CLIMATE, JOB SATISFACTION, AND WORK ENGAGEMENT AND THE EFFECT ON EMPLOYEE PERFORMANCE DURING THE COVID-19 PANDEMIC (STUDY AT PT PERKEBUNAN NUSANTARA VII KEDATON BANDAR LAMPUNG) - SARAGIH, DESTRI GRISELDA; Djuardi, Dian Komarsyah; Saptiani, Fenny (Jurnal Kompetitif Bisnis, 2022)
This study aims to determine the effect of organizational climate, job satisfaction, and work engagement on employee performance during the Covid-19 pandemic. This research uses a quantitative approach with the type of explanatory research. The sampling technique used was proportionate stratified random sampling, with a sample of 71 respondents from PT Perkebunan Nusantara VII Kedaton Bandar Lampung employees. Data were obtained from questionnaires distributed on a likert scale. Data analysis in this study used multiple linear analysis, with the help of SPSS 25. This study shows that simultaneously the organizational climate has a significant effect on employee performance, while job satisfaction, and work engagement have an insignificant effect on employee performance. Simultaneously, the organizational climate, job satisfaction, and work engagement together have a significant effect on employee performance at PT Perkebunan Nusantara VII Kedaton Bandar Lampung.